2017
DOI: 10.1080/10926771.2017.1322658
|View full text |Cite
|
Sign up to set email alerts
|

Links Between Stressful Life Events and Proactive and Reactive Functions of Aggression

Abstract: Recently, more attention has been devoted to understanding how stressful life events might relate to proactive and reactive aggression. Findings suggest that stressful life events are more strongly linked to reactive, than proactive, aggression; however, it is unclear whether the impact of stressful life events on proactive and reactive aggression might vary as a function of the level of exposure to or type of stressful life event. The current study examined how level of exposure to stressful life events (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
(25 reference statements)
2
12
0
Order By: Relevance
“…This high prevalence could be explained by the country's armed conflict or violent culture (Ember and Ember, 2005) that normalises negative interactions, such as the use of CP, as a disciplinary practice. Studies carried out in countries with a long history of armed conflict have shown that patterns of violence permeate the culture through such actions as sexual and partner violence and physical and emotional abuse in children (Brown et al, 2017; Grogan‐Kaylor et al, 2018). Likewise, Ember and Ember (2005) found that CP is related to higher societal violence, and that this violence explains CP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This high prevalence could be explained by the country's armed conflict or violent culture (Ember and Ember, 2005) that normalises negative interactions, such as the use of CP, as a disciplinary practice. Studies carried out in countries with a long history of armed conflict have shown that patterns of violence permeate the culture through such actions as sexual and partner violence and physical and emotional abuse in children (Brown et al, 2017; Grogan‐Kaylor et al, 2018). Likewise, Ember and Ember (2005) found that CP is related to higher societal violence, and that this violence explains CP.…”
Section: Discussionmentioning
confidence: 99%
“…This impulsive reaction by parents may be the result of a failure to control their emotions because of direct or indirect exposure to conflict or war, as suggested by Brown et al . (2017). In their study, they argued that interpersonal violent acts might have greater impacts on emotion regulatory processes, which are associated with reactive aggression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Raine et al [12] observed that school children with schizotypal traits were likely to suffer from peer victimization. There is also an association between adverse life events and aggression [29] Huang et al found that stressful life events increased the odds of aggression [30]. Considering the above studies, our third hypothesis is that adverse life events may be as important as childhood trauma in mediating the association between schizoid and aggression.…”
mentioning
confidence: 83%
“…The vast majority of these records are due to interpersonal violence defined as the deliberated use of human force related to the level of self-perceived thread characterized by the use of such force against oneself, other person, group of people, or community, with a high probability to cause injuries, death, psychological damages, developmental disorders, or deprivations (Krug, Dahlberg, Mercy, Zwi, & Lozano, 2003), which is presented to the extent that the subjects value a situation as stressful and are probably inclined by a hostile attitude to deal with it (Suldo, Shaunnessy, & Hardesty, 2008), or by an aggressive reactive or proactive response when experiencing or witnessing stressful situations (Brown, Fite, DiPierro, & Bortolato, 2017); leading to the performance of aggressive behaviors associated with violent behavior models with which subjects are identified (Potocnjak, Berger, & Tomicic, 2011), the lack of impulse control (Thompson & Auslander, 2011), the social support received in the moment of confrontation, and a pessimistic feeling in which other resolution alternatives (Seiffge-Krenke, Aunola, & Nurmi, 2009).…”
Section: Introductionmentioning
confidence: 99%